2018
DOI: 10.1007/s12298-018-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for accurate normalization of gene expression with quantitative real-time PCR in Haloxylon ammodendron under different abiotic stresses

Abstract: plays an important role in maintaining the structure and function of the entire ecosystem where it grows. No suitable reference genes have been reported in plants to date. In this study, a total of 8 reference genes (, ,, ,, ,- and ) were selected from the available trancriptome database, and the expression stability of these 8 candidate genes was validated under different abiotic stress with three different statistical algorithms (geNorm, NormFinder and BestKeeper). The results produced from different models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Selection of reference genes and verification of primer specificity. We selected 10 genes as candidate genes by mining the N. tangutorum transcriptome data according to previous reports on the selection of reference genes in model plants and non-model plants [13][14][15][16][17][18][19][20][21][22] . The chosen N. tangutorum genes were then used to query against the Arabidopsis protein database using BLASTX to obtain the homologous genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of reference genes and verification of primer specificity. We selected 10 genes as candidate genes by mining the N. tangutorum transcriptome data according to previous reports on the selection of reference genes in model plants and non-model plants [13][14][15][16][17][18][19][20][21][22] . The chosen N. tangutorum genes were then used to query against the Arabidopsis protein database using BLASTX to obtain the homologous genes.…”
Section: Resultsmentioning
confidence: 99%
“…However, with our increasing understanding of the agricultural ecological value of non-model plants, it has become important to study their molecular genetic mechanisms and to determine their appropriate reference genes under different experimental conditions. To date, some non-model plants have been selected for research on internal reference genes, including Reaumuria 16 , Caragana intermedia 17 , Setaria viridis 18 , Miscanthus lutarioriparia 19 , Haloxylon ammodendron 20 , Hylocereus undulatus Britt 21 , and Corchorus capsularis L 22 .…”
mentioning
confidence: 99%
“…This difference in reference gene evaluation could also be seen in Undaria pinnatifida [35]. However, studies have also been reported in which NormFinder and BestKeeper provided similar outcomes [36]. Multiple control reference genes are essential if possible [10].…”
Section: Discussionmentioning
confidence: 91%
“…The quantitative primers of the candidate reference genes were designed by the Primer3Plus online website (www.primer3plus.com/cgi-bin/dev/primer3plus.cgi). The parameters were as follows: the length of the primers and the amplification product size were [18][19][20][21][22][23][24][25][26][27] bp and 100-200 bp, respectively, the range of melting temperature (Tm) was 65°C-75°C, and the GC was 40%-60%. Primers were synthesized by Sangon Biotech.…”
Section: Selection Of Candidate Reference Genes and The Design Of Qrtmentioning
confidence: 99%
“…it has become important to study their molecular genetic mechanism, and to determine their appropriate reference genes under different experimental conditions. To date, some non-model plants have been selected for internal reference genes, including Reaumuria [16], Caragana intermedia [17], Setaria viridis [18], Miscanthus lutarioriparia [19], Haloxylon ammodendron [20], pitaya [21], and jute [22].…”
Section: Introductionmentioning
confidence: 99%